India’s Engagement in Development and Peacebuilding Assistance in the Post-Conflict States: An Assessment - Choedon, Yeshi (Frontiers in Political Science, 2021)
The emotional and ideological factor to express solidarity with the other developing countries is the main driving factor for India to engage in development assistance. In the changed geopolitical and geo-economic context in the globalized world, the economic factor of access to the market for Indian products and natural resources for its growing industrial sector became the additional motivation. As India does not subscribe to peacebuilding, it has no separate category of peacebuilding assistance. This paper’s central focus is on why India’s way of providing development and peacebuilding assistance captured the world’s attention in the 21st century and how India’s ways are different from that of the OECD’s Development Assistance Committee (DAC) countries. It highlights India’s unique guiding principles, approaches, and modalities for development and peacebuilding assistance. It focuses on why the developing countries appreciated India’s development and peacebuilding assistance, although it is not much in terms of volume compare to the DAC countries. It emphasizes the advantages of accepting diversity instead of an attempt for uniformity in peacebuilding assistance.